2021
DOI: 10.1111/bjd.20758
|View full text |Cite
|
Sign up to set email alerts
|

Combined carboplatin and paclitaxel therapy improves overall survival in patients with nivolumab‐resistant acral and mucosal melanoma

Abstract: F, Kirtschig G et al. Doxycycline versus prednisolone as an initial treatment strategy for bullous pemphigoid: a pragmatic, non-inferiority, randomised controlled trial. Lancet 2017; 389:1630-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Results were notable for a 12% response rate that was durable in certain cases. 35 In a retrospective study by Maeda et al, 36 the efficacy of carboplatin/paclitaxel treatment for ICI-resistant acral and mucosal BRAF wild-type melanomas was investigated. Patients who received second-line treatment with carboplatin/paclitaxel after progression on first-line treatment with nivolumab, ipilimumab, or nivolumab/ipilimumab combination therapy were evaluated for tumor response rates and survival.…”
Section: Negative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results were notable for a 12% response rate that was durable in certain cases. 35 In a retrospective study by Maeda et al, 36 the efficacy of carboplatin/paclitaxel treatment for ICI-resistant acral and mucosal BRAF wild-type melanomas was investigated. Patients who received second-line treatment with carboplatin/paclitaxel after progression on first-line treatment with nivolumab, ipilimumab, or nivolumab/ipilimumab combination therapy were evaluated for tumor response rates and survival.…”
Section: Negative Resultsmentioning
confidence: 99%
“…One-year OS was 50% for combined ipilimumab/nivolumab, 12.5% for ipilimumab alone, and 58.3% for carboplatin/paclitaxel. 36 One clinical scenario where chemotherapy may be considered is in patients with immunotherapy toxicity who have BRAF wild-type melanoma. A case study was published that described a patient with stage IV BRAF wild-type cutaneous melanoma who was treated with combination ipilimumab/nivolumab initially.…”
Section: Negative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since GNAQ mutations are drivers of mitogen-activated protein kinase (MAPK) activation similar to BRAF, new studies have identified selumetinib (a selective MEK inhibitor) as a possible therapy in metastatic uveal melanoma [ 15 ]. Furthermore, carboplatin and paclitaxel, two chemotherapeutic agents that were used in this case, have shown one-year overall survival and three-month progression-free survival in the nivolumab-refractory setting in one trial [ 16 ]. Reasonable responses were also seen in another trial, hence their use in our pregnant patient with PMML [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While chemotherapy is not the first-line treatment for advanced melanoma, it is often used after immunotherapy/targeted therapy failure in patients, and chemoresistance is one of the barriers to its effectiveness (American Cancer Society, 2022b; Goldinger et al, 2022;Kalal et al, 2017). PTX is part of the chemotherapy portfolio used in advanced melanoma (Samoylenko et al, 2016;Maeda et al, 2022), and its effectiveness can be dampened by various drug resistance mechanisms (Castro et al, 2022). The ability of the CM from the rHDL-DPM NPs-, and rHDL-DPM-DMXAA NPs-treated macrophages to modulate the proliferation and to improve the sensitivity of the B16-F10 cells to PTX suggest that the rHDL-DPM NPs could be a valuable tool in mitigating chemoresistance to PTX in B16-F10 tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%